Solvent-free thiophene-based electrolytes: synthesis of new liquid-crystalline ionic conductors for batteries: part I. Issue 44 (18th October 2018) - Bogdanowicz, Krzysztof Artur; Gancarz, Pawel; Filapek, Michal; Pociecha, Damian; Marzec, Monika; Chojnacka, Ida; Iwan, Agnieszka
Abstract : We report the synthesis of new liquid crystalline thiophene esters, ThBz1 and ThBz2, for use in lithium-ion batteries as new, safe, solvent-free ionic conductors. Abstract : New liquid crystalline thiophene esters, thiophene-3-yl 3, 4, 5-tris( n -dodecan-1-yloxy)benzoate (ThBz1) and thiophene-3-yl 3, 4, 5-tris[4-( n -dodecan-1-yloxy)benzyloxy]benzoate (ThBz2), were synthesized for use in lithium-ion batteries as safe, new solvent-free ionic conductors. Both compounds were synthesized in multi-step reactions and were characterized via 1 H, 13 C NMR and FT-IR spectroscopy, confirming the formation of the desired products. ThBz1 and ThBz2 showed good thermal stability and liquid crystalline behaviour. Electrochemical tests demonstrated a wide electrochemical window of 4 V for both tested ThBz compounds. Moreover, preliminary battery tests for new electrolytes in the LiCoO2 /Li4 Ti5 O12 system confirmed their applicability in lithium-ion batteries.